2021
DOI: 10.1101/2021.07.28.21261261
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictors of COVID-19 vaccination uptake and reasons for decline of vaccination: a systematic review

Abstract: Background: Various COVID-19 vaccines with proven safety and effectiveness are available now but vaccine hesitancy remains a public threat. COVID-19 vaccines uptake appears to have an essential role in the successful control of the COVID-19 pandemic. Objective: To examine predictors of COVID-19 vaccination uptake and reasons for decline of vaccination. Methods: We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines for this systematic review. We searched Medline, PubMed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 74 publications
(117 reference statements)
9
46
1
Order By: Relevance
“…In addition, we found that the most important reasons why participants were not vaccinated were concerns about the safety, effectiveness and side effects of COVID-19 vaccines, previous COVID-19 diagnosis, and females’ effort to get pregnant. Literature confirms this finding with studies conducted not only in the general population but also in patients and health professionals (Galanis et al, 2021).…”
Section: Discussionsupporting
confidence: 67%
“…In addition, we found that the most important reasons why participants were not vaccinated were concerns about the safety, effectiveness and side effects of COVID-19 vaccines, previous COVID-19 diagnosis, and females’ effort to get pregnant. Literature confirms this finding with studies conducted not only in the general population but also in patients and health professionals (Galanis et al, 2021).…”
Section: Discussionsupporting
confidence: 67%
“…Recent meta-analyses found that the overall COVID-19 vaccine acceptance rate was approximately 73%, while acceptance among the general population is higher than among healthcare workers ( Galanis et al, 2021 ; Luo et al, 2021 ; Snehota et al, 2021 ; Wang et al, 2021b ). Also, real-world data from early studies reveal that COVID-19 vaccination uptake ranges from 28.6% to 98% in the general population ( Galanis et al, 2021a ). Several factors influence vaccination intention and uptake in the general population such as sociodemographic characteristics, attitudes towards vaccination, psychological factors, perceptions of risk and susceptibility to COVID-19, knowledge, information, personal factors, medical conditions, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors influence vaccination intention and uptake in the general population such as sociodemographic characteristics, attitudes towards vaccination, psychological factors, perceptions of risk and susceptibility to COVID-19, knowledge, information, personal factors, medical conditions, etc. ( Al-Amer et al, 2021 ; Galanis et al, 2021a ; Snehota et al, 2021 ; Wake, 2021 ; Wang et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…Successful management of the pandemic requires vaccination of the general population at a high rate, which may now be as high as 80% (Bartsch et al, 2020). However, the COVID-19 vaccination rate exceeds 80% in only a few studies, and in some cases is extremely low, reaching as low as 28.6% (Galanis et al, 2021a). Until now, COVID-19 vaccine uptake in most countries fall below estimates of the required threshold for herd immunity (Ritchie et al, 2021).…”
Section: Introductionmentioning
confidence: 99%